Analisis Risk Analysis and Tsunami Disaster Mapping in Mamuju, West Sulawesi Using TUNAMI-N2 - Theresya Maharani Bandangan; Guntur Pasau; Gerald Hendrik Tamuntuan (Jurnal Ilmiah Sains, 2023)
Mamuju City is an area that has extraordinary natural beauty and is often used as a tourist attraction, especially marine tourism. The potential for a tsunami disaster in this region is very large because it is located directly opposite the Makassar Strait which is the location of the center of tectonic earthquakes. This study aims to determine the maximum height of tsunami waves and the arrival time of tsunami waves that can hit Mamuju City and analyze the risks that occur due to the tsunami waves. The method used in this study was modeling using TUNAMI-N2 software. The results of this study showed that a tsunami with an earthquake magnitude of 7,2 and  7.3 Mw had a maximum wave height of 7,91 m and 8.04 m at the 18th minute with a very high risk. Keywords: Disaster; model; risk; tsunami